Exploring bioactive peptides as potential therapeutic and biotechnology treasures: A contemporary perspective - Patil, Prasanna J.; Sutar, Shubham S.; Usman, Muhammad; Patil, Devashree N.; Dhanavade, Maruti J.; Shehzad, Qayyum; Mehmood, Arshad; Shah, Haroon; Teng, Chao; Zhang, Chengnan; Li, Xiuting (Life sciences (1973), 2022)
In preceding years, bioactive peptides (BAPs) have piqued escalating attention owing to their multitudinous biological features. To date, many potential BAPs exhibiting anti-cancer activities have been documented; yet, obstacles such as their safety profiles and consumer acceptance continue to exist. Moreover, BAPs have been discovered to facilitate the suppression of Coronavirus Disease 2019 (CoVID-19) and maybe ideal for treating the CoVID-19 infection, as stated by published experimental findings, but their widespread knowledge is scarce. Likewise, there is a cornucopia of BAPs possessing neuroprotective effects that mend neurodegenerative diseases (NDs) by regulating gut microbiota, but they remain a subject of research interest. Additionally, a plethora of researchers have attempted next-generation approaches based on BAPs, but they need scientific attention. The text format of this critical review is organized around an overview of BAPs' versatility and diverse bio functionalities with emphasis on recent developments and novelties. The review is alienated into independent sections, which are related to either BAPs based disease management strategies or next-generation BAPs based approaches. BAPs based anti-cancer, anti-CoVID-19, and neuroprotective strategies have been explored, which may offer insights that could help the researchers and industries to find an alternate regimen against the three aforementioned fatal diseases. To the best of our knowledge, this is the first review that has systematically discussed the next-generation approaches in BAP research. Furthermore, it can be concluded that the BAPs may be optimal for the management of cancer, CoVID-19, and NDs; nevertheless, experimental and preclinical studies are crucial to validate their therapeutic benefits. [Display omitted]